A note on the E-mail game: Bounded rationality and induction - Uwe Dulleck (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
In Rubinstein's (1989) E-mail game there exists no Nash equilibrium where players use strategies that condition on the E-mail communication. In this paper I restrict the utilizable information for one player. I show that in contrast to Rubinstein's result, in a payoff dominant Nash equilibrium players use strategies that condition on the number of messages sent. Therefore - induction under the assumption of bounded rational behavior of at least one player leads to a more intuitive equilibrium in the E-mail game.
urn:nbn:de:kobv:11-10064273
Keywords: C72; 330; Induction; Subgame Perfect Equilibrium; Information sets; Imperfect recall